Implementation and Optimization of a Smart Assistive Stick Using Ultrasonic Sensors for Enhanced Environmental Interaction and Obstacle Detection - Qutaiba Sabah Fadhil; Ali Adnan Ali; Noor Alhuda Falah Hassan; Abdullah Faris Salih (American Journal of Botany and Bioengineering, 2024)
The system has been successfully implemented and the aim is achieved without any complications. The results are realized in this project are genuine and are a product of sincerity and hard work. It is worth mentioning that such devices can be communicated in a perfect way, especially the Ultrasonic Sensor communicates well with the The surrounding environment is in several directions and is transmitted to the Arduino microcontroller successfully. It can be said that there are many obstacles and potholes and also going up or down stairs can be picked up involuntarily with this stick. There are many future prospects for the project, because the poor stratum of society needs support of all ages. The product can also be developed or modified according to the growing needs or requirements.